Growth in Sub-Saharan Africa - Ghura, Dhaneshwar (IMF Working Papers; Working Paper ;, 1995)
The paper investigates empirically the determinants of economic growth for a large sample of sub-Saharan African countries during 1981-92. The results indicate that (i) an increase in private investment has a relatively large positive impact on per capita growth; (ii) growth is stimulated by public policies that lower the budget deficit in relation to GDP (without reducing government investment), reduce the rate of inflation, maintain external competitiveness, promote structural reforms, encourage human capital development, and slow population growth; and (iii) convergence of per capita income occurs after controlling for human capital development and public policies.